The Influencing Factor Analysis of Stunting Incidence in Children Aged 24-59 Months At Kedung Jati Village (Public Health Perspective Journal, 2019)
Stunting is a chronic nutritional problem caused by lack of nutritional intake for a long time, because of giving food that is inappropriate with needs. In 2017, around 150,8 million or 22,2% toddlers in the world were stunting. Based on data from WHO, states that Indonesia is included in the top three countries with the highest stunting prevalence in the southeast Asia, with an average from 2005-2017 reaching 36,4%. The purpose of this study is to analyze the effect of nutritional intake, history of infectious diseases, environmental sanitation and immunization status of stunting incidence. This study is quantitative with a cross sectional approach, and it is using simple random sampling. The analysis calculation of this study is using path analysis. The result of this study on stunting variable were nutritional intake (p value = 0,000), history of infectious diseases (p value = 0,062) then hypothesis that immunization status direct effect the incidence of stunting is Ho, means rejected.